2004
DOI: 10.1074/jbc.m406591200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Missense Mutation in the Sodium Bicarbonate Cotransporter (NBCe1/SLC4A4) Causes Proximal Tubular Acidosis and Glaucoma through Ion Transport Defects

Abstract: In humans and terrestrial vertebrates, the kidney controls systemic pH in part by absorbing filtered bicarbonate in the proximal tubule via an electrogenic Na ؉ /HCO 3 ؊ cotransporter (NBCe1/SLC4A4). Recently, human genetics revealed that NBCe1 is the major renal contributor to this process. Homozygous point mutations in NBCe1 cause proximal renal tubular acidosis (pRTA), glaucoma, and cataracts (Igarashi, T., Inatomi, J., Sekine, T., Cha, S. H., Kanai, Y., Kunimi, M., Tsukamoto, K., Satoh, H., Shimadzu, M., T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
182
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(195 citation statements)
references
References 37 publications
7
182
1
1
Order By: Relevance
“…Measured and calculated acid-base transport properties of clones used in this study as previously reported for other transporters (24,66). "␤" is the buffering capacity in units of mM ϫ (pH unit)…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Measured and calculated acid-base transport properties of clones used in this study as previously reported for other transporters (24,66). "␤" is the buffering capacity in units of mM ϫ (pH unit)…”
Section: Tablementioning
confidence: 99%
“…Two-electrode Voltage Clamp-For these experiments, oocytes were injected with 0.5 ng of cRNA and membrane currents were recorded with an OC-725C voltage clamp (Warner Instruments, Hamden, CT), filtered at 2-5 kHz, digitized at 10 kHz. I-V protocols consisted of 40-ms steps from V h (Ϫ60 mV) to Ϫ160 and ϩ60 mV in 20-mV steps (23,24).…”
Section: Electrophysiologymentioning
confidence: 99%
“…Because NBC1 transports Ͼ1 HCO 3 Ϫ ion (2 or 3) per Na ϩ ion, the transport that is mediated by NBC1 is associated with a net movement of negative charge across the membrane. We and other researchers (4)(5)(6)(7)(8) have reported that inactivating mutations of the human NBC1 gene SLC4A4 cause proximal renal tubular acidosis associated with ocular abnormalities and stunted growth. Also, some patients with NBC1 mutations have elevated pancreatic enzyme levels and͞or mental retardation (4,5,7,8).…”
mentioning
confidence: 99%
“…These patients require larger doses of oral bicarbonate [10] or the intravenous infusion of a 3.75 % solution of sodium HCO 3 − at rates varying from 0.3 to 0.8 ml/min to cause an increment of 2-3 mEq/l/h of plasma HCO 3 − and to minimize extracellular volume expansion, as classically reported [24]. However, even if a normal plasma HCO 3 − concentration is not achieved, the verification of massive bicarbonaturia when plasma HCO 3 − is below normal levels is likely better evidence of defective proximal reabsorption [3,31]. The measurement of urine pCO 2 when the urinary pH is higher than that of blood is a sensitive index of distal nephron H + secretion.…”
Section: Functional Testsmentioning
confidence: 91%